Unpicking the role of acyl carrier proteins from polyketide synthases with mass spectrometry - Bellamy-Carter, Jeddidiah S. G. (2020)
Polyketide synthases (PKS) are multi-domain enzymes responsible for the biosynthesis of structurally and functionally diverse natural products. A particular subfamily—trans-AT PKSs—have modular architecture and account for much of this diversity. These have attracted much attention as targets for engineering tailored PKSs to produce feed-stocks or synthetically challenging organic compounds. Phylogenetic and subsequent experimental studies have shown that ketosynthases (KS), the key domains for catalysing polyketide elongation, from trans-AT PKSs are highly substrate specific and may mediate polyketide structure. Until recently, the acyl carrier proteins (ACP) of trans-AT PKSs have been seen as passive carriers of the growing polyketide chain.